Modern systems of government : exploring the role of bureaucrats and politicians - Farazmand, Ali (Sage Publications, 1997)
The success or failure of empires, nation-states and city-states often rests on the relationship between bureaucracy and politicians. In this provocative volume, Ali Farazmand examines the myriad relationships between politicians and bureaucrats. After introducing the basic elements of bureaucracies in Part One, the book examines the relations between bureaucrats and politicians in presidential and parliamentary systems. The contributors to the volume comprise a virtual `who's who' in the discipline.